MANAJEMEN PENDIDIKAN KARAKTER DALAM MENINGKATKAN MUTU PENDIDIKAN MADRASAH : Studi Multisitus di MI Miftahul Huda Lamong Badas dan MI Al Ifadah Ngunut Tulungagung - Sri Putrianingsih; Prim Masrokan Mutohar; Imam Fuadi (Center for the Research and the Community Service, Islamic Institut of Hasanuddin Pare - Kediri, 2023)
Abstract: A madrasas that has good education, will create charismatic that is good in the eyes of the community. Because the quality of madrasas is an issue that has always been a serios study in the world of education from time to time. Various approaches have been taken by the goverment and administrators of educational institutions to improve the quality of madrasas. One approach is caracter education at MI Miftahul Huda Lamong Badas, and MI Al Ifadah Ngunut Tulungagung,two institutions that both are also instilling character education foe all schoolchildren, especially students. This reasearch is aimed at finding answers to three basic questions; a) how is the manajement planing to improve the quality of madrasas based on character education, b). How to implement character education based madrasah quality improvement manajement, c) How to evaluate character education based madrasah quality improvement manjement, in MI Miftahul Huda lamong Badas and MI al Ifadah Ngunut Tulungagung. This study uses a qualitative approach with the type af multi site study. Sources of data are informants, events locations, and document. Data collection techniques with participant observation, in depth interviews and documentations. Dat analysis unsed of the data ins done through peer discussion, triangulation of data sources and triangulation of methods. Research findings 1) Madrasah quality improvement planning is a process of determining strategic target and program in improving the quality of madrasah based on character education; 2) the implementation of madrasas quality improvemen manajement is an act of learning and habutuation of character-based curiculum, extra program and madrasas program; 3) Evaluation uses an approach to achieving the madrasas vision and mission indicators. The results of the study suport Sallis’s opinion that the steps for quality improvement are identivication of customer , produc development. Also Sallis’s opinion that quality madrasas are madrasas that have high moral / character values, excellent test results, and care concern for student. Keyword : manajement, madrasas quality, character Education.